(untitled) (Scientific journal of the Fergana State University, 2025)
Respect is a fundamental concept that shapes human interaction, yet its linguistic expressions vary significantly across cultures. This study investigates how respect is encoded in English and Japanese through lexical, morphological, and syntactic structures, providing insights into the broader semantic networks that underpin these languages. Unlike previous studies, this research emphasizes novel examples, focusing on underexplored aspects such as indirectness in English politeness and verb conjugation nuances in Japanese honorifics. Using discourse analysis and corpus linguistics, the study highlights pragmatic speech acts, including requests, apologies, and gratitude, and examines the sociolinguistic functions of respect in maintaining social hierarchy and harmony. Findings reveal that while English relies on modal verbs and lexical markers to soften expressions, Japanese employs complex honorific systems that encode hierarchical relationships. These linguistic strategies reflect distinct cultural values and offer a framework for understanding respect as a dynamic, culturally situated phenomenon. This analysis enhances our understanding of intercultural communication and underscores the role of language in shaping social interactions.